1993
DOI: 10.1095/biolreprod49.5.1074
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Factor Activates Cyclic Adenosine 3′,5′-Monophosphate Phosphodiesterase in Xenopus Laevis Oocytes and Potentiates Progesterone-Induced Maturation via Cyclic Guanosine 5′-Monophosphate Accumulation

Abstract: Xenopus oocytes were found to express atrial natriuretic factor (ANF) receptors that activate guanylate cyclase and stimulate cyclic guanosine 5'-monophosphate (cGMP) production in a dose- and time-dependent manner. A truncated fragment of ANF, known to bind to mammalian ANF receptors without stimulating cGMP accumulation, did not elicit a cGMP response in oocytes. In addition, preincubation with ANF increased the number of oocytes that underwent progesterone-induced maturation. The maximally effective dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…cAMP phosphodiesterase (Sandberg et al 1993), but inhibits spontaneous rat oocyte maturation by cGMP accumulation (Törnell et al 1990). However, suppression of MAPK activation in Xenopus oocytes does not inhibit progesterone-induced GVBD, suggesting that the activation of MAPK is actually not necessary for the resumption of meiosis, and therefore, an alternative pathway may exist in frog oocytes for triggering the resumption of meiosis (Fisher et al 1999).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…cAMP phosphodiesterase (Sandberg et al 1993), but inhibits spontaneous rat oocyte maturation by cGMP accumulation (Törnell et al 1990). However, suppression of MAPK activation in Xenopus oocytes does not inhibit progesterone-induced GVBD, suggesting that the activation of MAPK is actually not necessary for the resumption of meiosis, and therefore, an alternative pathway may exist in frog oocytes for triggering the resumption of meiosis (Fisher et al 1999).…”
Section: Figurementioning
confidence: 99%
“…ANP can affect oocyte maturation by cGMP, i.e. ANP participates in ovum development by stimulation of cGMP accumulation and activation of cAMP-phosphodiesterase, and thereby promotes Xenopus ovum maturation (Sandberg et al 1993) and resumption of meiosis in hamster oocytes (Hubbard & Price 1988). On the other hand, ANP dose-dependently inhibits spontaneous maturation of rat oocytes via cGMP accumulation (Törnell et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Additional experiments such as those involving 8-Br-cGMP microinjections are needed to distinguish between these possibilities. Similarly, further analyses are required to determine if cGMP can also be elevated by particulate GC signaling (Sandberg et al 1993, Zhang et al 2005 and if NO's effects on nemertean oocytes fail to involve protein kinase G (PKG) activation and/or can utilize cGMP-independent mechanisms (Bilodeau-Goeseels 2007, Wang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This cAMP rise could in turn deactivate AMPK, perhaps via PKA-mediated S485/491 phosphorylation on AMPK (Stricker et al 2010a), although AMPK deactivation due to a drop in AMP as cAMP levels rise cannot be precluded. In either case, however, a PDE downregulation would be opposite to the cGMP-mediated stimulation of PDE activity in Xenopus oocytes (Sandberg et al 1993), where cGMP elevations can lower cAMP levels and enhance progesterone-induced GVBD, perhaps by targeting a PDE2 isotype (Sandberg et al 1993), rather than a PDE3 form, such as found in mice (Vaccari et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The rat ANP used in current studies may interact via ANP receptors found on the Xenopus oocytes membranes (Sandberg et al, 1993) as the amino acid sequences of frog ANP and mammalian ANP are similar (Lazure et al, 1988). Decrease in AQP4 water channel activity by ANP has potential relevance in many cells that express AQP4 since ANP is known to have important roles in the modulation of renal function and regulation of body fluid homeostasis (Lin, Chao and Chao, 1995 ;Palm et al, 1995).…”
mentioning
confidence: 99%